Strategi Komunikasi Guru Dalam Menumbuhkan Motivasi Belajar Siswa Kelas V SD Negeri 6 Pekanbaru - Safitri, Tia; Siti Quratul Ain (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2024)
The aim of this research is to find out how teachers' communication strategies increase learning motivation for class V students at SD Negeri 06 Pekanbaru. This type of research is descriptive qualitative research. This research was carried out on Teacher Communication Strategies in Growing Class V Students' Learning Motivation at SD Negeri 06 Pekanbaru. The collection techniques used in this research include: interviews, observation and documentation. The data analysis used is Miles and Huberman's qualitative data analysis. Based on the results of the data analysis that has been carried out, Teacher Communication Strategies in Fostering Learning Motivation for Class V Students at SD Negeri 06 Pekanbaru. It was found that teachers were able to apply verbal and non-verbal communication strategies well. However, students' motivation to learn is still low It is said that it does not match the aspects that have been researched and observed. As for signs such as a lack of student motivation in learning, student motivation still looks poor, this can be seen in students who are embarrassed to ask questions, tend to remain silent in class, do assignments lazily, play when given assignments by the teacher even though the learning environment is quite good and comfortable.